Effects of Genistein on Lipid Metabolism, Antioxidant Activity, and Immunity of Common Carp (Cyprinus carpio L.) Fed with High-Carbohydrate and High-Fat Diets. (31st March 2023) - Yang, Liping; Zhao, Mengjuan; Liu, Mingyu; Zhang, Wenlei; Zhi, Shaoyang; Qu, Leya; Xiong, Jinrui; Wang, Luming; Qin, Chaobin; Nie, Guoxing
Abstract : A 56-day feeding trial was conducted to investigate the effects of genistein on growth, lipid metabolism, antioxidant capacity, and immunity of common carp fed with high-carbohydrate or high-fat diets. Five diets were used to feed fish: control diet (5% fat; CO), high-fat diet (11% fat; HF), high-carbohydrate diet (45% carbohydrate; HC), and HF or HC diet with 500 mg/kg genistein (FG or CG). Results showed that final body weight (FW) and specific growth rate (SGR) were significantly reduced, but the supplementation with genistein resulted in higher values of FW and SGR than the HF or HC group. Both high carbohydrate and high fat belong to high-energy diets, which may promote lipid deposition. Genistein obviously decreased liver triglyceride (TG) content and alleviated hepatic fat vacuolation in the HF and HC groups. The expression of lipid metabolism genes ( cpt-1 and atgl ) was markedly higher in the FG group than in the HF group. The lipid synthesis-related genes ( fas, acc, and pparγ ) were elevated in high-energy diets but recovered to the control level or reduced after genistein treatments. With respect to fatty acid transporter genes, fatp increased in the FG group, and cd36 increased in the CG group. Furthermore, the antioxidant and immune indexes, such as total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-PX), superoxide dismutase (SOD), acid phosphatase (ACP), and lysozyme (LZM) activities, were decreased, while malonate aldehyde (MDA) content, activities of alanine aminotransferase (ALT), and aspartate aminotransferase (AST) were enhanced in the HF and HC groups. The antioxidant and immunity values could be ameliorated by treatment with genistein. Moreover, the transcript levels of antioxidant-related genes ( cat, gr, and nrf2 ) in the liver and anti-inflammatory factors ( tgf-β and il-10 ) and lyz in the head kidney tissue were promoted, although the expression levels of proinflammatory factors ( tnf-α and il-6 ) declined in the genistein supplementation group, which confirmed the antioxidant and immune-enhancing effects of genistein. Therefore, 500 mg/kg genistein could ameliorate the negative effects of high-energy diets on immunity.